2016
DOI: 10.1038/srep36138
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 (LCN2) is a promising target for cholangiocarcinoma treatment and bile LCN2 level is a potential cholangiocarcinoma diagnostic marker

Abstract: Cholangiocarcinoma (CCA) is a devastating disease due to resistance to traditional chemotherapies and radiotherapies. New therapeutic strategies against CCA are urgently needed. This study investigated the role of lipocalin-2 (LCN2) in human cholangiocarcinoma as a potential therapeutic target and diagnostic marker. So far, the role of LCN2 in cancer is still controversial and studies regarding the role of LCN2 in CCA are limited. LCN2 knockdown inhibited CCA cell growth in vitro and in vivo through induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 44 publications
2
28
1
Order By: Relevance
“…We have also used western blot analysis to validate the NGAL from conditioned media and to confirm its presence in plasma of cancer patients (unpublished data). Our result corresponds to a recent report on lipocalin-2 as a potential biomarker for CCA (27).…”
Section: Discussionsupporting
confidence: 92%
“…We have also used western blot analysis to validate the NGAL from conditioned media and to confirm its presence in plasma of cancer patients (unpublished data). Our result corresponds to a recent report on lipocalin-2 as a potential biomarker for CCA (27).…”
Section: Discussionsupporting
confidence: 92%
“…An interrogation of The Cancer Genome Atlas (TCGA) data portal showed that several cancers have significantly altered expression of LCN2 compared to normal tissue, suggesting LCN2's potential as a prognostic biomarker [39] (Figure 1). Some studies have correlated upregulated LCN2 expression in tumor tissue with poor outcomes caused by increased growth of cancer cells, therapeutic resistance, invasion, and metastasis [27,28,36,40,41]. Similarly, Bauer et al analyzed 207 well-characterized breast cancer tumor tissues by IHC and observed a significant correlation between high LCN2 levels and negative estrogen receptor expression [36].…”
Section: Lcn2 Expression In Cancermentioning
confidence: 99%
“…Recent research has shown that the transferrin-independent iron transport mechanism existed in the tumor microenvironment, and these transport mechanisms were dependent on the key molecules of lipocalin2 (LCN2) and siderophores [ 119 ]. LCN2 is also up-regulated in some cancers, including breast, cervical and pancreatic cancer, and LCN2 expression correlates with increased invasiveness and poor prognosis [ 89 , 90 , 91 , 92 ]. The expression of LCN2 influences the prostate cancer cells growth and invasion via activating ERK signaling pathway [ 90 , 120 ].…”
Section: Alterations Of Iron Homeostasis In Cancer Cellsmentioning
confidence: 99%